Universitas Islam Internasional Indonesia (UIII) and the Search for a New Epistemology in Islamic Studies - Ade Jaya Suryani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Formed through Presidential Regulation No. 57/2016, UIII represents a state initiative to globalise Indonesian Islam and to position it as an intellectual actor in the global academic landscape. This article aim to analyses the epistemological transformation in Indonesian Islamic scholarship through the establishment of the Universitas Islam Internasional Indonesia (UIII). By using document analysis of government policies, journalistic reports, the university’s official website, observation, and scholarly discourse, this study argues that UIII marks a paradigmatic shift in Indonesian Islamic higher education, from a normative-theological model towards a secular-academic epistemology with a global orientation. Nevertheless, this orientation also reveals ambiguities, for UIII simultaneously seeks to undertake a decolonial process, namely challenging Western paradigms on the one hand while embracing the Islamic intellectual tradition on the other. This analysis shows that UIII is situated within an epistemological tension that is not easily synthesised: the institution rejects the dominance of a single centre of knowledge, yet at the same time has not formulated a stable alternative epistemological form. Thus, UIII is more aptly understood as a dynamic space of epistemic negotiation, where various knowledge traditions compete and engage in dialogue to shape the future configuration of Indonesian Islamic scholarship.